Privacy and security impacts of social media on military cadets in Malaysia - Mohd. Shah Rizad Mohd Yusof (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2021)
Even though Military Armed Forces (MAF) has its security classifications which mirror the urgency of handling the official classified information such as restricted, confidential, secret or top-secret, other information which might involve national interest, also need to have a degree of protection or special handling. It portrays the need for having information security management of pertinent information, to protect official classified information from various threats, including information leakage through social media. Due to the increased use of social media, a significant amount of leakage cases have been reported worldwide. Realizing this current phenomenon and protecting MAF classified information, this research focuses on security and privacy concerns of using social media among Universiti Pertahanan Nasional Malaysia (UPNM) or National Defense University of Malaysia (NDUM) military cadets. The aim of this study is to investigate the use of social media among the military cadets and its impacts on the cadet's security and privacy. This research used a survey as the research method and questionnaires as the data collection instrument was distributed to 50 respondents who are active users of social media. This study also examined popular online social network sites among the cadets, their information security behaviour, the information they shared on social media, and their responses to scenarios which indicate their security awareness. The quantitative data were analysed using SPSS version 21. Based on the results, this study proposes an appropriate training programme regarding data disclosure on social media that tailored to the military cadets' behaviour and security awareness levels. The results revealed a relationship between the identified attributes, usage behaviour, security education and knowledge, security awareness, and influencing factors. The study also identified how military cadets' social environment shaped individuals' security and privacy awareness. It contributes to research and importance to society, particularly university students and military cadets because it is seen as an effort in promoting safe and secure use of social media.